Analisis Desain Komunikasi Visual pada Station Id Trans Media Group - Gurning, Linda RM; Rizkitysha, Talita Leoni (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Media Komunikasi Trisakti, 2017)
Information and communication is one of the most important necessity in daily life. Media is really affecting human perception side because the function of media is transmitting the information between one to another, not to mention television as an electronic media. Besides as an information transmitter, a television channel should have station ID as their branding environment. The visual of station ID made as aestheic as can be by not ignoring visual communication design rules. The method used in this thesis about Trans Media Station ID is qualitative descriptive method. This method was chosen because the information was obtained by interviewing informants whom are station ID designer and then be enligtened by descriptive method. After interviewing the informants, obtained information that the main concept of Trans 7 station ID is about the Indonesian culture, based on Trans 7 program are so thick with Indonesian culture. Meanwhile, the main concept of Trans TV station ID is Trans TV as the leading television who can be a determinant of Indonesian people show. Although Trnas TV and Trans 7 have different concept in their station ID, but still there are a common thread to their station ID, namely with using the same color, because the color use in station ID is corporate color from Trans Media logo.